Developing foresight through the evaluation and construction of vision statements: an experiential exercise - John Fiset; Melanie A. Robinson (Organization Management Journal, 2020)
Purpose – Scholars and practitioners generally acknowledge the crucial importance of visions in motivating and inspiring organizational change. In this article, we describe a two-part activity based on visionary leadership scholarship and theory designed to teach students to cultivate foresight and consider future possibilities through the organizational vision statement development process. Design/methodology/approach – Using an experiential design, the exercise draws on several empirically validated techniques to encourage foresight and future thinking, to help students place themselves in the shoes of the chief executive officer of a hypothetical organization and use dramaturgical character development strategies to craft the vision statements that they will champion. Findings – The exercise has been used in three different business courses (N = 87) and has been well received. Originality/value – The content of the exercise is adaptable to a variety of courses in which leadership and vision are focal topics – such as organizational behavior, strategy and leadership – and could also be modified for an online classroom setting.